Identification of the novel HLA‐B*38:97 allele in a Chinese individual. (24th November 2021) - Zhou, Xiao‐Yan; Kuang, Yi‐Qun; Zhang, Jian‐Bo; Li, Yu‐Ye
Abstract : Compared with the HLA‐B*38:02:01:01 allele, HLA‐B*38:97 differs by a single nucleotide substitution.